2016
DOI: 10.1177/1933719115616497
|View full text |Cite
|
Sign up to set email alerts
|

Density of Stromal Cells and Macrophages Associated With Collagen Remodeling in the Human Cervix in Preterm and Term Birth

Abstract: Remodeling of the cervix occurs in advance of labor both at term and at preterm birth. Morphological characteristics associated with remodeling in rodents were assessed in cervix biopsies from women at term (39 weeks' gestation) and preterm (<33 weeks' gestation). Collagen I and III messenger RNA and hydroxyproline concentrations declined in cervix biopsies from women in labor at term and preterm compared to that in the cervix from nonlaboring women. Extracellular collagen was more degraded in sections of cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 52 publications
(89 reference statements)
4
34
0
Order By: Relevance
“…In mice, cervix length is increased with fewer cell nuclei/area evident in stroma with pregnancy (Figure 1). A similar finding is evident in women before pregnancy compared to those pregnant whether or not in labor (15). Reduced cell nuclei density may reflect hypertrophy of cells or an increase in extracellular space.…”
Section: Cervix Anatomy and Function For Pregnancy In Mammals At The supporting
confidence: 65%
See 2 more Smart Citations
“…In mice, cervix length is increased with fewer cell nuclei/area evident in stroma with pregnancy (Figure 1). A similar finding is evident in women before pregnancy compared to those pregnant whether or not in labor (15). Reduced cell nuclei density may reflect hypertrophy of cells or an increase in extracellular space.…”
Section: Cervix Anatomy and Function For Pregnancy In Mammals At The supporting
confidence: 65%
“…These effects on remodeling were overshadowed by evidence that treatment caused fetal demise without preterm birth possible through impaired placental function led. Finally, a study of cervix biopsies from around 30 weeks of pregnancy reinforces the conclusion that resident macrophages were increased compared to that in women at term not in labor (15). The collective implication is that morphological evidence has accumulated to reinforce the concept that the presence and likely activity of macrophages are an essential part of the process that remodels the cervix in preparation for parturition.…”
Section: Ripeningmentioning
confidence: 54%
See 1 more Smart Citation
“…In human cervix, p38 activation has been associated with parturition but this is likely due to inflammatory cell traffic macrophages 6163 and or association with tissues such as the fetal membranes overlying the cervix at term 64, 65 as this tissue expresses an increased inflammatory signature. 66 …”
Section: Tissue Specific Regulation Of P38 and Implications For Nomentioning
confidence: 99%
“…(5565) However, although studies have shown an influx of immune cells into cervical tissue, it is unclear what triggers the immune cells to travel to the cervix. In addition, evidence from other studies suggest that immune cell activation is not vital for cervical ripening.…”
Section: Cervical Tissue Remodeling In Normal Pregnancymentioning
confidence: 99%